14 EXAMINING THE IMPACT OF SAFETY MONITORING DEVICES ON CARE WORK AND PROCESSES IN JAPANESE NURSING HOMES. (25th October 2022) - Obayashi, K; Kodate, N; Kondo, H; Okamoto, Y; Kaneko, H; Ishii, Y; Nonoda, T; Masuyama, S
Abstract: Background: Although the impact of new technology on the workplace has been discussed for many years, little has been reported regarding the effect of new technology in nursing homes. The aim of the research was to test the effect of a safety monitoring device on night-time work patterns. Methods: A monitoring sensor with an infrared camera was installed in Tokyo-based residential nursing homes in April 2020. A pre/post intervention and observation study was conducted before and after the introduction of the device. Four care professionals worked each night in pairs (one person providing care, and the other observing and keeping minute-by-minute records of task and time allocated to each task. The tasks were divided into 33 items). The data were collected by two pairs at three different nights for pre-intervention and from two pairs at two nights for post-intervention. Ten care professionals participated in the study, and they were looking after 30 older adults (86.8 +/- 6.8 years old). Results: The total time for executing various tasks marginally increased from 978 mins to 1033 mins. However, statistically significant changes were found mainly among items related to medical care and safety. While nurse call response time decreased significantly, the proportion of time allocated to personal care such as vital checks (from 1 to 2 percent) and mobility (from 4 to 9 percent) assistance doubled. Break time also increased significantly. Conclusion: While the introduction of a safety monitoring system did not radically reduce the workload, it changed the patterns of caregiving during the night shift. Some behavioural changes were directly caused by functions of the system, while others were by-products. Staff's break length also increased. The findings suggest that the introduction of Information and Communication Technology (ICT) in nursing homes has the potential to release time to care.